Studi Kelayakan Usaha Budidaya Ikan Bandeng di Kota Gresik Menggunakan Analisis SWOT Dan Kelayakan Finansial - Akhmad Wasiur Rizqi; Rafiq Putra Purnomo; Iqbal Putra Ramadhan (JURNAL AGROINDUSTRI HALAL, 2026)
Milkfish is a leading fishery commodity with increasing demand. Gresik Regency, as a coastal area and industrial area, faces challenges to the sustainability of its cultivation business due to land conversion and environmental pressures. This study aims to analyze the feasibility of milkfish cultivation at UD Tiga Saudara in Manyar District, Gresik Regency, from both non-financial and financial aspects. The research method uses a qualitative descriptive approach through SWOT analysis and a quantitative approach using Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). Data were obtained through field observations, interviews, questionnaires, and literature studies. The results of the study indicate that non-financially the business has dominant strengths and opportunities, while financially the NPV is Rp2,268,090,078, the IRR is greater than the 10% discount rate, and the Payback Period is 0.77 years. Thus, UD Tiga Saudara's milkfish cultivation business is declared feasible and prospective for sustainable development.